Assessment of the effect of injection magnesium sulphate on fetal heart rate pattern in patients of eclampsia and preeclampsia - Singh, Reeta; Rai, Nirupama; Sharma, Neela Rai; Mohan, Renu; Srivastava, Reena; Tiwari, Harish Chand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To assess the effect of injection magnesium sulphate on fetal heart rate pattern in severe preeclampsia and eclampsia. Methods: This is a hospital-based prospective observational study. It was conducted in the Dept. of Obstetrics and Gynaecology, BRD Medical College, Gorakhpur over period of one year from August 2014 to July 2015.Total 122 patients with diagnosis of severe preeclampsia and eclampsia who received injection MgSO4 were included in the study. Patients who delivered within 1 to 2 hrs of injection MgSO4, had pulmonary edema, respiratory depression, renal insufficiency, patients with recurrent convulsions not controlled by MgSO4 alone, fetus who had abnormal fetal heart rate pattern prior to administration of injection MgSO4, IUD baby, baby of gestetional age <28 weeks were excluded from the study. Fetal heart rate pattern tracings were taken by CTG machine before administration of injection magnesium sulphate. Injection magnesium sulphate was given according to Pritchard Regime. Fetal heart rate pattern after injection MgSO4 were compared with fetal heart rate pattern before injection magnesium sulphate regarding all four parameters fetal heart rate, variability, accelerations and deceleration. Results: Before injection magnesium sulphate mean fetal heart rate was 148.7 bpm+10.78. After 15 minutes mean fetal heart rate was 147.8 bpm+10.32.After 1hour, 2 hour and 4 hour of injection magnesium sulphate mean fetal heart rate was139.1 bpm+9.6,139.2 bpm+9.8 and 137 bpm+9.4 respectively which was statistically significant (p value <0.001). Only patients with good variability were included in the study. After 1 hour of injection magnesium sulphate 16.4%, after 2 hour 23% and after 4 hour 31.1 % developed poor variability i.e. <5. Before injection magnesium sulphate only 4% had no acceleration, after 15 minutes, 1 hour, 2 hour and 4 hour of injection magnesium sulphate 4.9%, 29.5%, 49% and 55% patients had no acceleration respectively. Before injection magnesium sulphate no patient had late deceleration. After 15 min only 2 patients had variable prolonged deceleration. After 1 hour, 2 hour and 4 hour 0%, 4.1% and 6.6% had late deceleration respectively. Conclusions: Maternal exposure to magnesium sulphate in severe preeclampsia and eclampsia is associated with persistent fall in baseline fetal heart rate by approximately 9-11 bpm which appeared at 1 hr of injection MgSO4 but it is within the accepted normal range (110 bpm - 160bpm). Statistically significant patients developed decreased beat to beat variability <5 after 1 hr of injection MgSO4. Statistically significant patients developed absent acceleration. Few patients developed late decelerations but it was not significant.